Canine benign hyperplasia prostate on male pug dog - Zulfa Ichsanniyati R. Ciwi Fadhlillah; I Nengah Yogiswari; Siti Zaenab; Deni Noviana; Sukmasari Arifah (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2019)
An 9-years-old male pug was examined for stranguria and letargic in one week. The dog has no testicles as the owner claimed that the dog had been castrated a few years ago. Abdominal palpation shows bladder retention filled with urine but no blockage was found. Urine sedimentation contained blood and few unknown crystal. Hematology showed mild anemia and leukocytosis while blood chemistry only found mild hyperglobulinemia. Radiography showed prostate enlargement. Ultrasound examination was showing mild nephrolithiasis, cystitis and prostatic enlargement. Diagnosis of benign prostate hyperplasia is suspected but doubtful because the animal has been castrated. Differential diagnose was prostatic cysts, infection and cancer. The dog received finasteride 1 mg/kg twice a day orally for 60 days and antibiotic. Urine catheter was temporarily installed to evacuate urine twice a day. Post treatment ultrasound was performed 20 days later and showed evident involution of prostate sizes. An enlarge irregular testicle was also found in right dorsolateral of bladder. Monorchid castration was performed at 60 days of finasteride. The dog was diagnosed with monorchid induce benign prostate hyperplasia from the radiography and ultrasonography. The prostate size was reduced after finasteride administration